Quadriláteros: construções geométricas com o uso de régua e compasso - Maziero, Lieth Maria (2011)
The objective of this research is to consider the professor continued formation, which background is a didactical sequence related to geometric constructions with a ruler and quadrilateral compass. The work developed intended to respond to the following research point: Is the use of geometric constructions with a ruler and a compass an instrument which favors the development of the geometry knowledge of the professors? The target public was made of primary mathematics professors. The research has a qualitative imprint, but we have especially considered the principles of the action research. For this research development we have relied on Ibermon (2010) and Shulman (1996) studies. The research results evaluation has disclosed difficulties on the part of these professors, related to the ruler and compass use, as well as the various figures properties articulation to be constructed as a way to justify such constructions. These findings are a sequence of activities to be used by primary school professors